2008
DOI: 10.1590/s1413-86702008000300010
|View full text |Cite
|
Sign up to set email alerts
|

Type IV SCCmec found in decade old Brazilian MRSA isolates

Abstract: Methicillin-resistant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…ST88 was the dominant clone among PVLpositive isolates. ST88 with PVL-positive isolates had been reported in Sweden, Brazil, Italy and Asia (Afroz et al, 2008;Fang et al, 2008;Reinert et al, 2008;Stefani et al, 2009). In China, this clone was the predominant lineages of PVL-positive clones and correlated to skin and soft tissue infection (Yao et al, 2010).…”
Section: Mlst-ccmentioning
confidence: 82%
“…ST88 was the dominant clone among PVLpositive isolates. ST88 with PVL-positive isolates had been reported in Sweden, Brazil, Italy and Asia (Afroz et al, 2008;Fang et al, 2008;Reinert et al, 2008;Stefani et al, 2009). In China, this clone was the predominant lineages of PVL-positive clones and correlated to skin and soft tissue infection (Yao et al, 2010).…”
Section: Mlst-ccmentioning
confidence: 82%
“…The patient remained hospitalized for 50 days and was discharged after treatment with clindamycin and gentamicin (Gelatti et al, 2009). Reinert et al (2008), analyzed a culture collection grown between 1995 and 1999 and characterized them by PFGE (electrophoresis in pulsed-field gel). The results showed that the predominant profile (80%) corresponded to the Brazilian Epidemic Clone (BEC).…”
Section: Case Reportsmentioning
confidence: 99%
“…These data showed that the presence of CA-MRSA in Brazil is longstanding and well established and must have passed unnoticed in clinical laboratories. It is necessary to detect and monitor these strains in the community and in hospitals for a better understanding of its epidemiology, as well as to inform public health strategies to control its spread (Reinert et al, 2008).…”
Section: Case Reportsmentioning
confidence: 99%
“…There are no data about the prevalence of SCCmec IV in Brazilian communities, but Reinert et al (22) characterized through pulsed-field gel electrophoresis (PFGE) a culture collection recovered between 1995 and 1999. The results showed that the predominant profile (80%) corresponded to the Brazilian endemic clone (BEC).…”
Section: S Aureus S Epidermidis S Saprophyticus S Haemolyticusmentioning
confidence: 99%
“…Even though the study was performed with hospital samples, these data showed that SCCmec IV has long been present in Brazil and must have passed unnoticed in the laboratory practice. These strains must be detected both in community and in the hospital to better elucidate their epidemiology and control their dissemination (22).…”
Section: S Aureus S Epidermidis S Saprophyticus S Haemolyticusmentioning
confidence: 99%